STRATEGI PEMASARAN DESA BRAJAN MENUJU DESA WISATA MANDIRI: MARKETING STRATEGY FOR BRAJAN VILLAGE TO BE INDEPENDENT TOURISM VILLAGE - Ivo Novitaningtyas; Andhatu Achsa; Budi Rahardjo (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
The objective of this research is to identify the existing business model implemented by Brajan Tourism Village by using Business Model Canvas (BMC) approach in order to develop a new business model after being analyzed by the SWOT analysis. SWOT analysis uses to identify the condition of internal factors based on the marketing mix of services and the conditions of external factors based on economic, environmental, political, socio-cultural, and technological conditions. The result shows that the condition of this tourism village has many strengths and some opportunities that have not been utilized. Thus, the formulation of strategies that can be applied is SO strategy, such as developing tourism products according to tourist interest trends, collaborating with tourism influencers as a promotion tool through social media, and increasing the quality and quantity of tourist facilities. The strategy should be implemented to develop a new business model for the Brajan Tourism Village in order to become an independent tourism village. Keywords: tourism village, marketing strategy, SWOT, business model canvas, Brajan